2019
DOI: 10.1103/physrevx.9.041032
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Engines Driven by Active Matter: Energetics and Design Principles

Abstract: Because of its nonequilibrium character, active matter in a steady state can drive engines that autonomously deliver work against a constant mechanical force or torque. As a generic model for such an engine, we consider systems that contain one or several active components and a single passive one that is asymmetric in its geometrical shape or its interactions. Generally, one expects that such an asymmetry leads to a persistent, directed current in the passive component, which can be used for the extraction of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 99 publications
5
116
0
Order By: Relevance
“…Since the work of self-driven particles of Viscek et al 15 , the modeling of active agents has been possible following a series of rules for particle interactions, such as alignment, polarization, repulsion, and quorum-sensing 13 , 16 . These interactions often give rise to the understanding of unexpected phenomena such as collective motion, turbulence, giant fluctuations, rectification, and self-organization 16 20 , and at the same time, they reproduce what we observe in nature. At the micro-scale, agents can be modeled as active Brownian particles (ABP), where ABP can take up energy from the environment to store it in an internal depot and convert it internal energy into kinetic energy and motion 21 .…”
Section: Introductionsupporting
confidence: 67%
“…Since the work of self-driven particles of Viscek et al 15 , the modeling of active agents has been possible following a series of rules for particle interactions, such as alignment, polarization, repulsion, and quorum-sensing 13 , 16 . These interactions often give rise to the understanding of unexpected phenomena such as collective motion, turbulence, giant fluctuations, rectification, and self-organization 16 20 , and at the same time, they reproduce what we observe in nature. At the micro-scale, agents can be modeled as active Brownian particles (ABP), where ABP can take up energy from the environment to store it in an internal depot and convert it internal energy into kinetic energy and motion 21 .…”
Section: Introductionsupporting
confidence: 67%
“…Recent works have shown that, in nonequilibrium dynamics, the current fluctuations are bounded by the coarse-grained entropy production rate [37][38][39][40][41]. In active fluids, there is no average current of particles provided that no asymmetric external potential is applied [68][69][70]. Yet, the bound on current fluctuations can still be formulated within the mapping of section 3.…”
Section: Efficiency and Transportmentioning
confidence: 99%
“…Stochastic thermodynamics has progressively evolved into an essential tool in the study of non-equilibrium systems as it connects the quantities of interest in traditional thermodynamics, such as work, heat and entropy, to the properties of microscopically resolved fluctuating trajectories [ 1 , 2 , 3 ]. The possibility of equipping stochastic processes with a consistent thermodynamic and information-theoretic interpretation has resulted in a number of fascinating works, with the interface between mathematical physics and the biological sciences proving to be a particularly fertile ground for new insights (e.g., [ 4 , 5 , 6 , 7 , 8 ]). The fact that most of the applications live on the small scale is not surprising, since it is precisely at the microscopic scale that fluctuations start to play a non-negligible role.…”
Section: Introductionmentioning
confidence: 99%